The Effect of Organizational Changes on the Psychosocial Work Environment: Changes in Psychological and Social Working Conditions Following Organizational Changes - Fløvik, Lise; Knardahl, Stein; Christensen, Jan Olav (Frontiers in Psychology, 2019)
Purpose The present study aimed to clarify the prospective effects of various types and frequencies of organizational changes on aspects of the psychosocial work environment. Methods The study had a prospective, full-panel, repeated measures design. Data were collected by self-administered, online questionnaire, with a two-year interval between measurement occasions. Five types of organizational change were assessed – company restructuring, downsizing, layoffs, partial closure, and partial outsourcing. The effects of change on eleven, specific work factors were measured utilizing QPS Nordic. At baseline, 12652 employees participated, while 8965 responded at follow-up. Generalized estimating equations (GEE) were utilized to estimate the effects of change taking place within the last 12 months or more than 24 months prior. Results Cross-sectional analyses, i.e. changes occurring within the last twelve months, showed all eleven work factors to be statistically significantly associated with the organizational changes restructuring, downsizing, and partial closure (coefficients ranging -.28 to .04). In the prospective analyses, i.e. the effects of change taking place more than 24 months prior, associations were no longer significant for a number of work factors, although all types of organizational change remained significantly associated with at least three work factors (coefficients ranging -.14 to .05). Following repeated organizational changes, statistically significant associations were shown for all eleven work factors (coefficients ranging from .39 to -.04). Conclusions Following both separate and repeated organizational change, various psychological and social work factors were altered, with the most pronounced effects following repeated change. These results suggest the implementing organizational change, especially repeated change, may have an adverse effect on various parts of the psychosocial work environment. The negative effects of a company’s psychosocial working conditions may contribute to the adverse health effects often observed following such changes and help explain why many change initiatives fail to reach its intended results.